Tracing The Economy-Wide Impact Of Agricultural Drought In The Northern Cape: A Social Accounting Matrix (SAM)-based Multiplier Analysis - Jules, Kane (School of Economics, 2024)
This paper uses a 2004 provincial social accounting matrix (SAM) to conduct a multiplier analysis that simulates the impact on the Northern Cape economy of an exogenous shock to the agricultural sector (such as a drought). By analysing the ripple effects of agricultural drought, this exercise highlights the multiplier effects (direct, indirect and induced effects) that manifest through the backward and forward linkages between agriculture and other related economic sectors. Through analysis of the multiplier effects on various sectors and the provincial economy as a whole, the study finds that the negative 10 percent exogenous shock to agricultural commodities exerts significant indirect effects throughout the Northern Cape economy. Sectors involved in the production of intermediate goods and consumer goods were found to experience the largest decline in response to the agricultural shock. In line with expectations, unskilled labourers and their dependent communities were found to experience the bulk of the distributional impact. However, impacts to the income of skilled labourers as well as services sectors were found to be particularly sensitive to the inclusion of enterprises as an endogenous account. Furthermore, the results suggest that expanding farmers' and households' access to credit can be a helpful short-term tool to limit the induced effects of the shock.